2017
DOI: 10.1063/1.4997483
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of surface recombination by electrochemical tuning of TiO2-passivated photocatalysts

Abstract: We present a systematic study of photoluminescence (PL) spectroscopy of TiO2-passivated GaAs as a function of electrochemical potential in an ionic liquid solution. We observe a 7X increase in the PL intensity as the GaAs transitions from accumulation to depletion due to the applied potential. We attribute this to the excellent control over the surface Fermi level enabled by the high capacitance of the electrochemical double layer and TiO2. This allows us to control the surface carrier concentration and corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…46 Carrier concentrations and nonradiative recombination rates also mattered. 47 Meyer et al reported electrical and optical properties of porous nanocrystalline TiO 2 films and found that charge accumulated in Ti 3+ trap states. 48 Jaramillo et al described hierarchically branched TiO 2 nanorod structures with enhanced carrier collection efficiency.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…46 Carrier concentrations and nonradiative recombination rates also mattered. 47 Meyer et al reported electrical and optical properties of porous nanocrystalline TiO 2 films and found that charge accumulated in Ti 3+ trap states. 48 Jaramillo et al described hierarchically branched TiO 2 nanorod structures with enhanced carrier collection efficiency.…”
mentioning
confidence: 99%
“…Carrier diffusion path lengths may limit catalytic activity, highlighting the importance of nanostructuring. , Surface modifications were found to enhance PEC performance by passivation of surface states . Carrier concentrations and nonradiative recombination rates also mattered . Meyer et al reported electrical and optical properties of porous nanocrystalline TiO 2 films and found that charge accumulated in Ti 3+ trap states .…”
mentioning
confidence: 99%